PERBAIKAN KAWASAN PERUMAHAN KUMUH DENGAN MEMPERGUNAKAN DANA KOMERSIAL (STUDI KASUS: KAWASAN TAMANSARI, BANDUNG) - Bagas Dwipantra Putra; Nia Kurniasih Pontoh (Institut Teknologi Sains Bandung, 2019)
The presence of slum settlement in urban areas is one of the phenomenant faced by many cities in developing countries. Slum improvement program in Indonesia has been started since Dutch colonization period and still continues until today. Most of the fund were used for the programs can be classified as grant. This kind of fund does not educate slum dwellers because it is not necessary for them to repay those fund. Also this type of fund are very limited in numbers, that is why it is so important to find another source that is sustainable and unlimited. The solution is by using commercial fund from formal banking institution, in this case housing loan. This research aim is to study the use of commercial fund for slum settlement improvement in Tamansari, Bandung. The result from this research is a concept for slum settlement improvement in Tamansari that emphasize on several aspect, such as cooperation and financial aspect. Financial Engineering is the most important indicator, that is used to indicate if this program is feasible from financial aspect.